Association Between Introduction of the 23-valent Pneumococcal Polysaccharide Vaccine (PPSV23) and Pneumonia Incidence and Mortality Among General Older Population in Japan: A Community-based Study - Aya Sugiyama; Masaaki Kataoka; Kentaro Tokumo; Kanon Abe; Hirohito Imada; Bunlorn Sun; Golda Ataa Akuffo; Tomoyuki Akita; Shingo Fukuma; Noboru Hattori; Junko Tanaka (Journal of Epidemiology)
Background: With global aging, especially in Asia, preventing pneumonia among seniors is vital. The necessity of introducing pneumococcal vaccines among the elderly has been highlighted, but there is a paucity of community-based real-world evidence on their effect. Sera Town in Hiroshima Prefecture, a super-aged community, launched a distinctive pneumococcal vaccination support project for elderly residents and conducted a 5-year follow-up survey. This study evaluates the effectiveness of this vaccination initiative. Methods: From October 2010 to March 2015, Sera Town recruited elderly residents for PPSV23 vaccination with partial cost subsidies. Participants were surveyed annually for 5 years post-vaccination to assess pneumonia incidence, calculated on a person-years basis. Using vital statistics from 2000 to 2016, we quantified changes in mortality rates associated with the vaccination support project through an interrupted-time-series analysis. Results: Of approximately 7,900 residents aged 65 and older, 3,422 (43%) participated in the project (median age: 84 years; range: 70–114 years; 56.7% female). Over 14,559 person-years of observation, 295 participants developed pneumonia. The post-vaccination incidence rate was 20.3 per 1,000 person-years (95% confidence interval [CI], 18.0–22.7). Interrupted time series analysis indicated a 25% reduction in Sera Town’s pneumonia mortality rate post-project, reversing an annual increase of 0.23 per 1,000 population pre-project to an annual decrease of 0.04 per 1,000 population post-project. Conclusion: This study provided real-world evidence on the association with PPSV23 vaccination on the general elderly through a community-based study. The results may be particularly useful for regions where PPSV23 serotypes are prevalent, offering insights for areas facing aging challenges.